Effects of monensin sodium and Xylanase on broiler growth performance - Hill, Cassidy A.; Delfelder, C.J.; Beyer, R. Scott; Stark, Charles R.; Evans, C.E.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2017)
Antimicrobials are used to fight against bacteria, viruses, fungi and protozoa, which is why they are used virtually everywhere. But, because of this excessive use there is an increasing pressure from the consumer to limit usage in poultry feeds. One potential alternative to replace the monensin sodium antimicrobial is exogenous xylanase, an enzyme which is used to improve nutrient digestibility in higher fiber poultry diets. Therefore, the objective of this research project was to evaluate the ability of xylanase replacing monensin sodium to improve nutrient digestibility of the higher fiber diets. Within this project there were a total of 216 Cobb 1-day old chicks (6 birds/cage and 6 cages/treatment) that were randomly assigned to a treatment, which served as the fixed effect, and cage, which served as the experimental unit. The corn and wheat based diets consisted of 0.10 g/kg monensin sodium (Coban 90; Elanco Animal Health, Greenfield, IN) or 16,000 betaxlylanse units/kg beta 1-4, endo-xylanase enzyme (Econase XT; AB Vista, Marlborough, UK). The 6 dietary treatments consisted of: 1) corn-based control diet; 2) wheat-based control diet; 3) corn-based with monensin sodium only; 4) wheat-based with monensin sodium only; 5) corn-based with xylanase only; and 6) wheat-based with xylanase only. The birds were fed on an ad libitum system for 21 days, with body weight and feed intake being recorded weekly to determine overall weight gain, total feed intake and feed conversion ratio. Once recorded, the data was then analyzed using the GLIMMIX procedure of SAS. Final body weight, feed intake and feed conversion ratio were impacted by the treatment (P < 0.01). The corn-based control diet (P < 0.05) improved feed conversation ratio compared to the wheat-based control diet but the added antimicrobial treatments of xylanase or monensin sodium did not affect the corn-based when added. In the wheat-based diet, xylanase (P < 0.05), but not monensin sodium (P > 0.05) improved FCR compared to the wheat-based control. The monensin sodium showed little impact potentially due to the controlled environment of caged batteries. But this project does suggest that xylanase improves the carbohydrate digestibility in wheat-based diets in this research project setting.
Keywords: Spring 2017